Mountains of water the terraces and traditions of the Ifugao - Corre, Fruto; Rodrigo, Nancy Pe.; Santos, Benilda (Makati Bookmark Video, 1998)
This documentary shows how the Ifugaos created and maintained the Ifugao Rice Terraces, the greatest agricultural achievement in human history. It also presents the Ifugao culture: the rituals of the mumbaki, the Hudhud chanted at harvest, the intricate art of weaving and woodcarving.
VHS.
Also issued in Filipino: Ifugao : bulubunduking buhay.
Narrators, Irma Adlawan-Marasigan and Pen Medina.
Keywords: Environmental science; Tourism; Anthropology